A medium-chromium high-strength steel with excellent oil-resistance and hydrogen-induced crack resistance, and preparation method and application thereof
The formation of fine and diffuse composite oxysulfides by specific components and Ti-RE composite alloying is solved, and the problem of insufficient anti-cooking oil corrosion and hydrogen-induced crack resistance of high-strength steel is achieved, and the low-cost high-efficiency corrosion resistance is achieved, which is suitable for high-corrosion environments.
Patent Information
- Application Number
- CN202310971886.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-08-03
AI Technical Summary
The existing high-strength steels are insufficient in anti-cooking oil corrosion and hydrogen-induced crack resistance, and the alloying of Ni, Mo and Cu leads to high alloy costs.
A medium-chromium high-strength steel with specific components is used, including 0.011%
It significantly improves anti-cooking oil corrosion and hydrogen-induced crack resistance, reduces material costs, and is suitable for high-corrosion environments.
Smart Images

Figure CN117230388B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials, and specifically relates to a medium-chromium high-strength steel with excellent resistance to oil corrosion and hydrogen-induced cracking, and a preparation method and application thereof. Background Art
[0002] Crude oil, especially high-sulfur and high-acid crude oil, has a serious impact on the corrosion of steel cargo tanks, threatening the safety of oil tanker operations. In addition, there is also the problem of corrosion on the upper deck of the cargo tank. A large number of studies have found that the uniform corrosion of the upper deck of the cargo tank has the following characteristics: (1) high concentration of H2S gas on the top of the tank; (2) the impedance effect of the oil film; (3) the destructive effect of retained water and tank washing on the oil film; (4) high acidity in the pitting pit; (5) the equiaxed nature of the pitting pit.
[0003] There are many factors that cause HIC in steel. Generally, as the pH value in the environment decreases, the HIC sensitivity of steel increases. Therefore, the increase of acidic gas CO2 will also increase the HIC sensitivity. In addition, if the solution contains Cl - It will also reduce the steel's resistance to HIC. In addition, temperature also has a significant effect on the HIC performance of steel.
[0004] In addition to the great influence of the environment on HIC of steel, the chemical composition, microstructure, segregation and non-metallic inclusions of the steel itself also have a great influence on its HIC performance. The increase of C, Mn, S and P content in steel reduces its anti-HIC sensitivity, while Cu and Mo increase its anti-HIC sensitivity. Jin et al. [Jin TY, Liu ZY, Cheng Y F. Effect of non-metallic inclusions on hydrogen-induced cracking of API5L X100 steel[J]. International Journal of Hydrogen Energy 2010, 35:8014-8021] found that non-metallic inclusions rich in Al and Si easily lead to HIC in X100 pipeline steel, and HIC extends along the non-metallic inclusions; Huang Feng et al. [Huang Feng, Liu Jing, Deng Zhao Jun, el al. Effect of microstructure andinclusions onhydrogen induced cracking susceptibility and hydrogen trappingefficiency of X120 pipeline steel [J]. Materials Science and Engineering A2010, 527:6997-7001.] found that the increase of granular bainite and MA component content in the microstructure or the increase of inclusion number and volume fraction will aggravate the HIC sensitivity of X120 pipeline steel; Zhou Qi et al. [Zhou Qi, Ji Genshun, Zhang Jianbin, et al. Sulfide inclusions and hydrogen-induced cracking in pipeline steel [J]. Materials Engineering 2002, 9:37-39.] found that long strips of MnS can significantly reduce the HIC resistance of pipeline steel.
[0005] Due to the high-concentration H2S gas at the top of the cargo oil tank in an oil tanker and the presence of chloride ions in the stagnant water at the bottom, the essence of its corrosion is mainly chloride ion corrosion and hydrogen-induced cracking. Chloride ion corrosion is mainly related to the corrosion-active inclusions in the material. Hydrogen-induced cracking is mainly related to the type of microstructure of the material. Acicular ferrite is considered to be an ideal microstructure for resisting hydrogen-induced cracking [Huang Feng, Liu Jing, Deng Zhao Jun, el al. Effect of microstructure and inclusions on hydrogen induced cracking susceptibility and hydrogen trapping efficiency of X120 pipeline steel [J]. Materials Science and Engineering A 2010, 527:6997-7001.]. Therefore, the present invention will mainly use the density of corrosion-active inclusions and the saturation current density at the static electrode potential (Е = -300 mV) to evaluate the resistance to local corrosion, and use the quantity of acicular ferrite to evaluate the resistance to hydrogen-induced cracking. Summary of the Invention
[0006] To solve the deficiencies of the prior art, the present invention provides a medium-chromium high-strength steel with excellent resistance to crude oil corrosion and hydrogen-induced cracking, as well as its preparation method and application. The present invention can solve the problems of insufficient resistance to crude oil corrosion and hydrogen-induced cracking of traditional high-strength steels, and the high alloy cost brought about by alloying with Ni, Mo, and Cu.
[0007] The technical solution provided by the present invention is as follows:
[0008] A medium-chromium high-strength steel with excellent resistance to crude oil corrosion and hydrogen-induced cracking, the chemical composition of which is calculated by mass percentage as follows: 0.011 < C < 0.069%, 0.11 < Si < 0.29%, 0.011 < Mo + Cu < 0.49%, 1.51 < Cr < 1.99%, 0.041 < Ti < 0.059%, 0.005 < RE < 0.019%, S ≤ 0.0010%, and the rest is Fe and inevitable impurities. At the same time, the above chemical composition also satisfies the formula: by mass percentage, Cu / Mo = 1 - 2.
[0009] The medium-chromium high-strength steel with excellent resistance to crude oil corrosion and hydrogen-induced cracking provided by the above technical solution can form fine, dispersed, and uniform complex oxysulfides, and has a significantly reduced density of corrosion-active inclusions, and has a significantly improved resistance to crude oil corrosion.
[0010] At the same time, the medium-chromium high-strength steel with excellent oil corrosion resistance and hydrogen-induced cracking resistance provided by the above technical solution can significantly improve the ability to resist hydrogen-induced cracking HIC (Hydrogen Induced Cracking) due to the use of specific content of Cr and RE.
[0011] At the same time, the medium-chromium high-strength steel provided by the above technical solution has excellent oil corrosion resistance and hydrogen-induced crack resistance and has high strength.
[0012] The roles of various elements in medium chromium high strength steel with excellent resistance to oil corrosion and hydrogen-induced cracking are as follows:
[0013] C element: C element is one of the most basic elements added to steel. Its solid solution strengthening and precipitation strengthening can significantly affect the mechanical properties of steel. However, C will significantly reduce the local corrosion performance of steel. At the same time, C is not conducive to the welding performance of steel. Under normal circumstances, the carbon content of steel with excellent welding performance must be strictly controlled. The C content in low-alloy high-strength steel is generally required to be less than 0.20%. Therefore, the carbon content in the steel of the present invention is 0.011-0.069%.
[0014] Si element: Si can inhibit the generation of acid in the rust layer and prevent Cl - In the inner rust layer, Si mainly exists in the form of divalent oxides in spinel oxides. Higher Si is conducive to refining α-FeOOOH in the rust layer, making the inner rust layer dense and thus hindering Cl - At the same time, the Si element is dissolved in ferrite and austenite to strengthen the steel and improve its mechanical properties. However, if the Si element in the matrix exceeds a certain range, it will promote the nucleation of grain boundary ferrite, inhibit the formation of acicular ferrite, and increase the percentage of MA components in the steel. Excessive Si is not conducive to the plasticity and toughness of the steel, and also reduces the welding performance of the steel. Therefore, the silicon content in the steel of the present invention is 0.11-0.29%.
[0015] Cr element: As the Cr content in steel increases, α-FeOOH can be effectively refined. When the Cr content in α-FeOOH exceeds 5%, it can prevent the entry of corrosive anions, such as Cl - , thereby improving the steel's resistance to oil corrosion and hydrogen-induced cracking. At the same time, the enrichment of Cr in the rust layer increases the electrode potential of the matrix. Therefore, the chromium content in the steel of the present invention is 1.51-1.99%.
[0016] Cu element: Cu element is one of the commonly added alloy elements in corrosion-resistant steel, and the general addition range is 0.3%-0.5%. Adding Cu element to seawater corrosion-resistant steel can not only slow down the local corrosion caused by S-containing inclusions and improve the corrosion resistance of steel, but also improve the flowability of molten steel. The role of Cu element in the corrosion resistance of steel is due to Cu. 2+ The copper content in the steel of the present invention is 0.011-0.49%.
[0017] Mo element: Mo is an important alloying element in steel and is widely used in the fields of alloy structural steel, stainless steel, tool steel and heat-resistant steel. Mo can significantly improve the pitting resistance of stainless steel and corrosion-resistant steel. In addition, Mo has the following main functions in steel: improving the strength and toughness of steel (especially high temperature performance), improving the corrosion resistance of steel in acid and alkali solutions and marine environments, improving the hardenability and hardenability of steel parts, purifying grain boundaries and improving delayed fracture resistance, etc. Therefore, the molybdenum content in the steel of the present invention is 0.011-0.49%.
[0018] Ti element: Ti has low solubility in steel and is mainly precipitated in the form of C and N compounds. Ti is generally added to carbon steel for microalloying, and the content addition range generally does not exceed 0.05%. When the temperature is high, Ti forms carbonitrides with C and N that are insoluble in austenite, which effectively inhibit the growth of austenite grains during heating, pin the grain boundaries, and refine the austenite grains; at lower temperatures, fine and dispersed nanoscale precipitates are formed, which pin dislocations and precipitate strengthening. Excessive Ti content increases the precipitation temperature of TiC and TiN, and the particles grow and coarsen rapidly, reducing the ability to pin grain boundaries and dislocations, and reducing the strength and toughness of the steel. Therefore, the titanium content in the steel of the present invention is 0.041-0.059%.
[0019] RE elements: The main functions of RE elements in the steel matrix are as follows: purifying molten steel, modifying inclusions, and microalloying. Purifying molten steel: Rare earths have extremely strong chemical reactivity, so they are very easy to combine with sulfur and oxygen elements in molten steel to form high-melting-point compounds, which precipitate from the molten steel to purify the molten steel. In addition, rare earths also have strong deoxidation ability, which is stronger than Mg, Al, and Ti elements and is comparable to Ca element, and its desulfurization ability is also very strong, second only to Ca element. Modifying inclusions: Adding rare earth elements to steel can change the shape, size, and distribution of inclusions formed in steel, and at the same time react with inclusions to change the types of inclusions. It replaces harmful inclusions in steel to improve the mechanical properties of the steel matrix and effectively improve the corrosion resistance of steel. Rare earth elements have strong metallicity and preferentially combine with sulfur elements to eliminate the formed MnS inclusions, and make the inclusions spheroidized and dispersed, effectively controlling the types, morphologies, and distribution of inclusions formed. Microalloying: Adding rare earth elements to steel can play a role in solid solution strengthening. In addition, rare earths refine the structure by inhibiting the recrystallization and growth of deformed austenite grains. Rare earth elements combine with hydrogen elements to reduce the sensitivity to hydrogen-induced cracks, and interact with C, N, V and other elements to change the phase transformation points of steel structure formation. Therefore, the rare earth content in the steel of the present invention is 0.005 < RE < 0.019%, and lanthanum or cerium, or a mixed rare earth of lanthanum and cerium can be specifically selected.
[0020] S element: S is a harmful element in steel. It is easy to form lamellar segregation of sulfides, which greatly reduces the strength and plasticity in the plate thickness direction (Z direction) and often causes lamellar tearing. S also easily generates low-melting-point FeS, causing hot cracking during hot rolling and welding of steel. Therefore, effective desulfurization processes must be adopted during smelting to ensure that the S content is controlled within a lower range, so that the steel may have excellent toughness and welding performance. Therefore, the sulfur content in the steel of the present invention is S ≤ 0.0010%.
[0021] Specifically, the microstructure type of medium-chromium high-strength steel is a composite microstructure type of acicular ferrite and polygonal grain boundary ferrite, where the area ratio of acicular ferrite ≥ 85%.
[0022] Specifically, the density of corrosion-active inclusions in medium-chromium high-strength steel ≤ 2 pieces / mm 2 .
[0023] Specifically, the saturation current density of medium-chromium high-strength steel at the static electrode potential E = -300 mV ≤ 5.0 mA.
[0024] The present invention also provides a preparation method of medium-chromium high-strength steel with excellent anti-corrosion performance against crude oil and anti-hydrogen-induced crack performance, including the following steps:
[0025] 1) Smelt, refine, and vacuum-treat molten steel in sequence, and then continuously cast it into billets;
[0026] 2) Perform conventional heating and equalization on the ingot;
[0027] 3) The ingot is continuously rolled into a product steel plate, and the final rolling temperature is controlled to be 750-850°C, and the steel is cooled to 410-550°C by water after rolling;
[0028] 4) Allow the steel plate to cool naturally to room temperature.
[0029] The smelting of step 1) specifically includes the following steps: adjusting the temperature and composition of the molten steel after steelmaking with molten iron, scrap steel, or molten iron and scrap steel in a converter or an electric arc furnace, adjusting the tapping temperature to 1585-1675°C, and the free oxygen content in the molten steel to 150-390ppm; stirring the molten steel with micro-sub-bubbles for 4-8 minutes after entering the ladle, and then pre-deoxidizing with Fe-Si alloy or Fe-Si-Mn alloy in the ladle, adjusting the free oxygen content in the molten steel to 50-90ppm, stirring with micro-sub-bubbles for 4-6 minutes, and then finally deoxidizing with Ti-RE composite alloy to obtain molten steel meeting the chemical composition; adding the Ti-RE composite alloy to the molten steel in the form of block alloy or cored wire, and the particle size of the Ti-RE composite alloy is 8-16mm; the addition amount of the Ti-RE composite alloy is 1.2-4.8kg per ton of molten steel.
[0030] Specifically, the refining method is to perform VD refining or RH refining after LF refining, and the refined molten steel is continuously cast according to a conventional process.
[0031] The present invention also provides the application of medium-chromium high-strength steel with excellent oil corrosion resistance and hydrogen-induced crack resistance as crude oil cargo tank material, inferior crude oil refining pipeline material, tobacco processing container material, tobacco processing pipeline material, hydrogen transportation pipeline material or hydrogen transportation container material.
[0032] The medium chromium high-strength steel provided by the present invention can be widely used in the above-mentioned scenarios due to its resistance to oil corrosion, resistance to hydrogen-induced cracking and high strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Optical micrograph of corrosion active inclusions;
[0034] Figure 2 Potentiodynamic polarization curve of the sample;
[0035] Figure 3 The electrochemical impedance test diagram of the sample, which includes the impedance diagram part, the bode diagram part and the phase angle diagram part in sequence;
[0036] Figure 4 Equivalent circuit of sample electrochemical impedance spectroscopy. DETAILED DESCRIPTION
[0037] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0038] Example 1
[0039] A medium chromium high-strength steel with excellent oil-resistant and hydrogen-induced cracking resistance, the chemical composition of which is as follows by mass percentage: C 0.035%, Si 0.15%, Mo 0.15%, Cu 0.29%, Cr 1.71%, Ti 0.045%, RE 0.012%, S0.009%, and the rest is Fe and unavoidable impurities.
[0040] The smelting and refining method is as follows: the temperature and composition of the molten steel are adjusted after steelmaking by a converter, the tapping temperature is adjusted to 1635°C, and the free oxygen content in the molten steel is 271ppm; after the molten steel enters the ladle, micro-sub-bubble stirring is used for 6 minutes, and then Fe-Si alloy is used in the ladle for pre-deoxidation, and the free oxygen content in the molten steel is adjusted to 70ppm, and after micro-sub-bubble stirring for 5 minutes, Ti-RE alloy is used for final deoxidation; Ti-RE alloy is added to the molten steel in the form of block alloy, and the particle size of the Ti-RE alloy is 12mm; the addition amount of Ti-RE composite alloy is 2.9kg per ton of molten steel, and then the molten steel is subjected to LF refining and RH refining.
[0041] LF Refining:
[0042] The viscosity of the refined slag is controlled at 1.55-1.95 Pa·s to improve the slag system's ability to absorb inclusions, thereby improving the cleanliness of the molten steel; the basicity of the white slag of the refining furnace is controlled at 5.3≤R≤7.5, which is beneficial to improving the desulfurization rate, improving the cleanliness of the molten steel, and reducing oxide inclusions in the molten steel; the MI slag index (=CaO / SiO2:Al2O3 ratio) is controlled at MI>0.153, and the distribution coefficient of sulfur is greatly increased, thereby controlling the appropriate fluidity of the refined slag at a certain basicity; the white slag holding time is 14.5min, the refining cycle is 39.5min, and the soft blowing time is guaranteed to be 4.5min, thereby controlling the outgoing [O] content.
[0043] RH Vacuum Treatment:
[0044] The vacuum chamber pressure was pumped down to below 66.7 kPa and maintained for 13.45 min. The bottom blowing argon flow rate was 14.95 m 3 / h to achieve 4 cycles of molten steel; strictly control the type and weight of added alloys, use higher-grade low-carbon ferromanganese, metallic manganese, low-carbon ferrosilicon, ferrotitanium and other alloys to ensure that the molten steel composition is fully qualified, and ensure that the vacuum is maintained for more than 5.1 minutes after the alloy is added to obtain purer molten steel; at the same time, provide a suitable molten steel temperature for continuous casting to ensure that the superheat of the tundish is 20.05℃ above the liquidus.
[0045] The refined molten steel is then continuously cast according to conventional processes: the temperature of the continuous casting tundish is 1541°C and the casting speed is 1.15 m / s.
[0046] The rolling process is as follows: heating and equalizing the ingot at 1190°C, with the ingot staying in the furnace for 3.5 hours; continuously rolling it into a product steel plate, and controlling the final rolling temperature to 790°C, cooling it to 480°C by water after rolling; naturally cooling it to room temperature and setting it aside.
[0047] The microstructure of the steel plate obtained by the above method is acicular ferrite + polygonal grain boundary ferrite, and the acicular ferrite accounts for 87%; the density of corrosion active inclusions in the steel plate is 1.2 / mm 2 ; The saturation current density of the steel plate at the static electrode potential (Е= -300mV) is 2.4mA.
[0048] The yield strength of the steel plate is 375MPa, the tensile strength is 530MPa, and the elongation is 35%. Chloride ion corrosion is mainly related to the corrosion active inclusions in the material, and hydrogen-induced cracking is mainly related to the microstructure type of the material. Acicular ferrite is considered to be an ideal microstructure for resistance to hydrogen-induced cracking. Since the microstructure is a uniform organizational structure with acicular ferrite as the main body (87%), it is also excellent in resistance to hydrogen-induced cracking.
[0049] Example 2
[0050] A medium chromium high-strength steel with excellent oil-resistant and hydrogen-induced cracking resistance, the chemical composition of which is as follows by mass percentage: C 0.063%, Si 0.27%, Mo 0.13%, Cu 0.28%, Cr 1.95%, Ti 0.057%, RE 0.017%, S0.009%, and the rest is Fe and unavoidable impurities.
[0051] The smelting and refining method is as follows: the temperature and composition of the molten steel are adjusted after steelmaking by a converter, the tapping temperature is adjusted to 1670°C, and the free oxygen content in the molten steel is 385ppm; after the molten steel enters the ladle, micro-sub-bubble stirring is used for 7 minutes, and then Fe-Si alloy is used in the ladle for pre-deoxidation, and the free oxygen content in the molten steel is adjusted to 85ppm, and after micro-sub-bubble stirring for 6 minutes, Ti-RE alloy is used for final deoxidation; Ti-RE alloy is added to the molten steel in the form of block alloy, and the particle size of Ti-RE alloy is 15mm; the amount of Ti-RE alloy added is 4.5kg per ton of molten steel, and then the molten steel is subjected to LF refining and RH refining.
[0052] LF Refining:
[0053] The viscosity of the refined slag is controlled at 1.51-1.91 Pa·s to improve the slag system's ability to absorb inclusions, thereby improving the cleanliness of the molten steel; the basicity of the white slag of the refining furnace is controlled at 5.1≤R≤7.3, which is beneficial to improving the desulfurization rate, improving the cleanliness of the molten steel, and reducing oxide inclusions in the molten steel; the MI slag index (=CaO / SiO2:Al2O3 ratio) is controlled at MI>0.155, and the distribution coefficient of sulfur is greatly increased, thereby controlling the appropriate fluidity of the refined slag at a certain basicity; the white slag retention time is 14.3min, the refining cycle is 39.3min, and the soft blowing time is guaranteed to be 4.6min, thereby controlling the outgoing [O] content.
[0054] RH Vacuum Treatment:
[0055] The vacuum chamber pressure was evacuated to below 66.6 kPa and maintained for 13.4 min. The bottom blowing argon flow rate was 14.9 m 3 / h to achieve 5 cycles of molten steel; strictly control the type and weight of added alloys, use higher-grade low-carbon ferromanganese, metallic manganese, low-carbon ferrosilicon, ferrotitanium and other alloys to ensure that the molten steel composition is fully qualified, and ensure that the vacuum is maintained for more than 5.3 minutes after the alloy is added to obtain purer molten steel; at the same time, provide a suitable molten steel temperature for continuous casting to ensure that the superheat of the tundish is 19.8°C above the liquidus.
[0056] The refined molten steel is then continuously cast according to conventional processes: the temperature of the continuous casting tundish is 1543°C and the casting speed is 1.11 m / s.
[0057] The rolling process is as follows: heating and equalizing the ingot at 1210°C, with a residence time in the furnace of 3.3 hours; continuously rolling it into a product steel plate, and controlling the final rolling temperature to 835°C, cooling it to 537°C after rolling by pouring water; naturally cooling it to room temperature and setting it aside.
[0058] The microstructure of the steel plate obtained by the above method is acicular ferrite + polygonal grain boundary ferrite, and the acicular ferrite accounts for 86%; the density of corrosion active inclusions in the steel plate is 1.59 / mm 2 ; The saturation current density of the steel plate at the static electrode potential (Е= -300mV) is 2.87mA.
[0059] The yield strength of the steel plate is 380MPa, the tensile strength is 535MPa, and the elongation is 34%. Chloride ion corrosion is mainly related to the corrosion active inclusions in the material, and hydrogen-induced cracking is mainly related to the microstructure type of the material. Acicular ferrite is considered to be an ideal microstructure for resistance to hydrogen-induced cracking. Since the microstructure is a uniform organizational structure with acicular ferrite as the main body (86%), it is also excellent in resistance to hydrogen-induced cracking.
[0060] Example 3
[0061] A medium chromium high-strength steel with excellent oil-resistant and hydrogen-induced cracking resistance, the chemical composition of which is as follows by mass percentage: C 0.018%, Si 0.25%, Mo 0.15%, Cu 0.32%, Cr 1.95%, Ti 0.043%, RE 0.009%, S0.008%, and the rest is Fe and unavoidable impurities.
[0062] The smelting and refining method is as follows: after steelmaking, scrap steel is treated in an electric arc furnace, and the temperature and composition of the molten steel are adjusted, the tapping temperature is adjusted to 1610°C, and the free oxygen content in the molten steel is 185ppm; after the molten steel enters the ladle, micro-sub-bubble stirring is used for 4 minutes, and then Fe-Si-Mn alloy is used in the ladle for pre-deoxidation, and the free oxygen content in the molten steel is adjusted to 57ppm, and after micro-sub-bubble stirring for 4 minutes, Ti-RE alloy is used for final deoxidation; Ti-RE composite alloy is added to the molten steel in the form of cored wire, and the particle size of the Ti-RE alloy is 9mm; the amount of Ti-RE composite alloy added is 1.4kg per ton of molten steel, and then the molten steel is subjected to LF refining and VD refining.
[0063] LF Refining:
[0064] The viscosity of the refined slag is controlled at 1.53-1.93 Pa·s to improve the slag system's ability to absorb inclusions, thereby improving the cleanliness of the molten steel; the basicity of the white slag of the refining furnace is controlled at 5.2≤R≤7.5, which is beneficial to improving the desulfurization rate, improving the cleanliness of the molten steel, and reducing oxide inclusions in the molten steel; the MI slag index (=CaO / SiO2:Al2O3 ratio) is controlled at MI>0.157, and the distribution coefficient of sulfur is greatly increased, thereby controlling the appropriate fluidity of the refined slag at a certain basicity; the white slag retention time is 14.4 minutes, the refining cycle is 39.5 minutes, and the soft blowing time is guaranteed to be 4.7 minutes, thereby controlling the outgoing [O] content.
[0065] RH Vacuum Treatment:
[0066] The vacuum chamber pressure was evacuated to below 66.5 kPa and maintained for 13.2 min. The bottom blowing argon flow rate was 14.9 m 3 / h to achieve 6 cycles of molten steel; strictly control the type and weight of added alloys, use higher-grade low-carbon ferromanganese, metallic manganese, low-carbon ferrosilicon, ferrotitanium and other alloys to ensure that the molten steel composition is fully qualified, and ensure that the vacuum is maintained for more than 5.2 minutes after the alloy is added to obtain purer molten steel; at the same time, provide a suitable molten steel temperature for continuous casting to ensure that the superheat of the tundish is 19.9°C above the liquidus.
[0067] The refined molten steel is then continuously cast according to conventional processes: the temperature of the continuous casting tundish is 1539°C and the casting speed is 1.21 m / s.
[0068] The rolling process is as follows: heating and equalizing the ingot at 1215°C, with the ingot staying in the furnace for 3.4 hours; continuously rolling it into a product steel plate, and controlling the final rolling temperature to 788°C, cooling it to 486°C after rolling by pouring water; naturally cooling it to room temperature and setting it aside.
[0069] The microstructure of the steel plate obtained by the above method is acicular ferrite + polygonal grain boundary ferrite, and the acicular ferrite accounts for 89%; the density of corrosion active inclusions in the steel plate is 1.37 / mm 2 ; The saturation current density of the steel plate at the static electrode potential (Е= -300mV) is 1.93mA.
[0070] The yield strength of the steel plate is 390MPa, the tensile strength is 550MPa, and the elongation is 33%. Chloride ion corrosion is mainly related to the corrosion active inclusions in the material, and hydrogen-induced cracking is mainly related to the microstructure type of the material. Acicular ferrite is considered to be an ideal microstructure for resistance to hydrogen-induced cracking. Since the microstructure is a uniform organizational structure with acicular ferrite as the main body (89%), it is also excellent in resistance to hydrogen-induced cracking.
[0071] Comparative Example 1
[0072] A medium chromium high-strength steel with excellent oil-resistant and hydrogen-induced cracking resistance, the chemical composition of which is as follows by mass percentage: C 0.035%, Si 0.15%, Mo 0.15%, Cu 0.29%, Cr 1.49%, Ni 0.58%, Al 0.035, S 0.009%, and the rest is Fe and unavoidable impurities.
[0073] The smelting and refining methods are as follows: after steelmaking, the molten iron is molten in a converter and then the temperature and composition of the molten steel are adjusted, the tapping temperature is adjusted to 1631°C, and the free oxygen content in the molten steel is 301ppm; after the molten steel enters the ladle, micro-sub-bubble stirring is used for 6 minutes, and then pure aluminum blocks are used in the ladle for pre-deoxidation and final deoxidation, the free oxygen content in the molten steel is adjusted to 4ppm, and then the molten steel is subjected to LF refining and RH refining.
[0074] LF Refining:
[0075] The viscosity of the refined slag is controlled at 1.53-1.94 Pa·s to improve the slag system's ability to absorb inclusions, thereby improving the cleanliness of the molten steel; the basicity of the white slag of the refining furnace is controlled at 5.15≤R≤7.42, which is beneficial to improving the desulfurization rate, improving the cleanliness of the molten steel, and reducing oxide inclusions in the molten steel; the MI slag index (=CaO / SiO2:Al2O3 ratio) is controlled at MI>0.153, and the distribution coefficient of sulfur is greatly increased, thereby controlling the appropriate fluidity of the refined slag at a certain basicity; the white slag holding time is 14.5min, the refining cycle is 39.5min, and the soft blowing time is guaranteed to be 4.55min, thereby controlling the outgoing [O] content.
[0076] RH Vacuum Treatment:
[0077] The vacuum chamber pressure was evacuated to below 66.67 kPa and maintained for 13.4 min. The bottom blowing argon flow rate was 14.8 m 3 / h to achieve 4 cycles of molten steel; strictly control the type and weight of added alloys, use higher-grade low-carbon ferromanganese, metallic manganese, low-carbon ferrosilicon, ferrotitanium and other alloys to ensure that the molten steel composition is fully qualified, and ensure that the vacuum is maintained for more than 5.35 minutes after the alloy is added to obtain purer molten steel; at the same time, provide a suitable molten steel temperature for continuous casting to ensure that the superheat of the tundish is 19.7℃ above the liquidus.
[0078] The refined molten steel is then continuously cast according to conventional processes: the temperature of the continuous casting tundish is 1542°C and the casting speed is 1.18 m / s.
[0079] The rolling process is as follows: heating and equalizing the ingot at 1190°C, with a residence time of 3.3 hours in the furnace; continuously rolling it into a product steel plate, and controlling the final rolling temperature to 791°C, cooling it to 483°C by water after rolling; naturally cooling it to room temperature for standby use.
[0080] The microstructure of the steel plate obtained by the above method is acicular ferrite + polygonal grain boundary ferrite, and the acicular ferrite accounts for 86%; the density of corrosion active inclusions in the steel plate is 11 / mm 2 The saturation current density of the steel plate at the static electrode potential (Е = -300mV) is 6.4mA. The yield strength of the steel plate is 365MPa, the tensile strength is 515MPa, and the elongation is 32%.
[0081] Comparative Example 2
[0082] A medium chromium high-strength steel with excellent oil-resistant and hydrogen-induced cracking resistance, the chemical composition of which is as follows by mass percentage: C 0.0358%, Si 0.17%, Mo 0.13%, Cu 0.27%, Cr 1.63%, Ti 0.041%, RE 0.013%, S0.008%, and the rest is Fe and unavoidable impurities.
[0083] The smelting and refining method is: after steelmaking, the molten iron is molten in a converter and then the temperature and composition of the molten steel are adjusted, the tapping temperature is adjusted to 1633°C, and the free oxygen content in the molten steel is 289ppm; after the molten steel enters the ladle, micro-sub-bubble stirring is used for 5 minutes, and then pure aluminum blocks are used in the ladle for pre-deoxidation and final deoxidation, the free oxygen content in the molten steel is adjusted to 5ppm, and then the molten steel is subjected to LF and RH refining.
[0084] LF Refining:
[0085] The viscosity of the refined slag is controlled at 1.59-1.98 Pa·s to improve the ability of the slag system to absorb inclusions, thereby improving the cleanliness of the molten steel; the basicity of the white slag of the refining furnace is controlled at 5.31≤R≤7.42, which is beneficial to improving the desulfurization rate, improving the cleanliness of the molten steel, and reducing oxide inclusions in the molten steel; the MI slag index (=CaO / SiO2:Al2O3 ratio) is controlled at MI>0.151, and the distribution coefficient of sulfur is greatly increased, thereby controlling the appropriate fluidity of the refined slag at a certain basicity; the white slag holding time is 14.18min, the refining cycle is 39.47min, and the soft blowing time is guaranteed to be 4.68min, thereby controlling the outgoing [O] content.
[0086] RH Vacuum Treatment:
[0087] The vacuum chamber pressure was evacuated to below 66.57 kPa and maintained for 13.4 min. The bottom blowing argon flow rate was 14.79 m 3 / h to achieve 5 cycles of molten steel; strictly control the type and weight of added alloys, use higher-grade low-carbon ferromanganese, metallic manganese, low-carbon ferrosilicon, ferrotitanium and other alloys to ensure that the molten steel composition is fully qualified, and ensure that the vacuum is maintained for more than 5.27 minutes after the alloy is added to obtain purer molten steel; at the same time, provide a suitable molten steel temperature for continuous casting to ensure that the superheat of the tundish is 19.78°C above the liquidus.
[0088] The refined molten steel is then continuously cast according to conventional processes: the temperature of the continuous casting tundish is 1541°C and the casting speed is 1.17 m / s.
[0089] The rolling process is as follows: heating and equalizing the ingot at 1180°C, with the ingot staying in the furnace for 3.6 hours; continuously rolling it into a product steel plate, and controlling the final rolling temperature to 785°C, cooling it to 485°C after rolling by pouring water; naturally cooling it to room temperature and set it aside.
[0090] The microstructure of the steel plate obtained by the above method is acicular ferrite + polygonal grain boundary ferrite, and the acicular ferrite accounts for 85%; the density of corrosion active inclusions in the steel plate is 16 / mm 2 The saturation current density of the steel plate at the static electrode potential (Е = -300mV) is 7.4mA. The yield strength of the steel plate is 370MPa, the tensile strength is 520MPa, and the elongation is 31%.
[0091] The corrosion resistance of the medium chromium high-strength steel with excellent oil corrosion resistance and hydrogen-induced crack resistance prepared in Example 1 is analyzed and tested, and the results are as follows:
[0092] 1. Test methods
[0093] The method for determining the density of corrosion active inclusions is as follows: the polished sample is corroded with a corrosive solution, the ratio of the corrosive solution is 100ml ethanol solution containing: 5.0ml concentrated hydrochloric acid, 0.012gCuCl2, 0.06gSnCl2, 3.0gFeCl3, the treatment time is 7s, blow dry, and then use an optical microscope to count the number of pitting pits at 100 times.
[0094] The electrochemical corrosion experiment environment is room temperature, and the corrosion liquid is 3.5% NaCl solution to simulate the corrosion environment. The electrode adopts the classic three-electrode system. The sample is the working electrode, the platinum electrode is the auxiliary electrode, and the saturated calomel electrode is the reference electrode (SCE). The electrochemical equipment is a ZAHNER electrochemical workstation, and the parameters are set using Thales electrochemical software. The workstation is connected to a computer for data display.
[0095] The electrochemical corrosion experiment was carried out at room temperature, and the potentiodynamic polarization curve (Tafel) and electrochemical impedance spectroscopy (EIS) of the small sample were tested. Before the test, the sample was immersed in the corrosion solution for 40 minutes, and the electrochemical impedance spectroscopy and potentiodynamic polarization tests were performed after the open circuit potential (OCP) was stabilized. The transition signal of the sine wave applied by the electrochemical impedance spectroscopy was 10mV, and the test scanning range was 10mHz~10kHz. The scanning rate of the potentiodynamic polarization curve was 0.5mV / s, and the scanning range was -600mV~1.2V. The potentiodynamic polarization curve and electrochemical impedance curve were fitted using origin and Zsimpwin software, respectively.
[0096] The AC impedance method disturbs the electrode system with small-amplitude sinusoidal waves of different frequencies. The equivalent circuit of the electrode is inferred through the relationship between the electrode system response and the disturbance signal. The parameters of each component in the equivalent circuit are fitted to obtain the corrosion kinetic parameters of the material. The factors affecting the corrosion resistance of the material can be analyzed intuitively and quantitatively, and the corrosion behavior of the material can be further understood.
[0097] The corrosion electrochemical experiments were all carried out in a classic three-electrode system, with the electrochemical sample to be tested as the working electrode, the saturated calomel electrode (SCE) as the reference electrode, and the platinum sheet as the counter electrode. The test temperature was 25 °C. At room temperature, the base metal was welded, and the sample was first immersed in the corrosion solution to test the open circuit potential (OCP). The test time was 40 minutes, and the electrochemical impedance test was started after the open circuit potential stabilized. The amplitude of the sine wave applied by the electrochemical AC impedance was 10mV, the scanning frequency range was 10mHz~10kHz, and the scanning time was 40 minutes.
[0098] 2. Test results and analysis
[0099] Figure 1 This is an optical micrograph of corrosion active inclusions in invention steel. It can be seen from the photo that there are very few corrosion active inclusions in invention steel. According to the measurement, the density of corrosion active inclusions in invention steel is 1.2 / mm 2 .
[0100] like Figure 2 As shown, there is no obvious passivation zone in the anode area of the polarization curve, indicating that no obvious passivation film is formed on the sample and the electrode activity is only controlled by activation.
[0101] Table 1 Potentiodynamic polarization curve fitting results of samples
[0102]
[0103] Figure 3 The AC impedance test results of the samples. Figure 3 From the Nyquist plot, we can see that the impedance arc is composed of a single capacitive reactance arc in the high and medium frequency bands, reflecting the capacitance characteristics, and no obvious inductive reactance arc is observed in the low frequency band. Figure 3 From the Bode diagram and phase angle diagram, we can see that there is only one peak. Combined with the Nyquist diagram, we can see that there is only one time constant, indicating that there is only one relaxation process in the electrode system that affects the state variable. Therefore, we can use Figure 4 A simple equivalent circuit diagram is used to simulate the corrosion process at different temperatures. In the circuit diagram, Rs represents the resistance of the corrosion solution, Q represents the constant phase angle element related to the double-layer capacitance, and considering the "diffusion effect" caused by the microscopic unevenness of the working electrode surface, the error is smaller when the constant phase angle element is used instead of the pure capacitance. Rct represents the charge transfer resistance. Figure 4The AC impedance spectrum equivalent circuit diagram is fitted, and the fitting results are shown in Table 2. The constant phase angle index n in the table reflects the degree of deviation between the actual capacitance and the ideal capacitance. The larger the value of n, the smaller the degree of deviation from the ideal capacitance. Generally, the n value of the double-layer capacitance of the corrosion electrode is between 0.5 and 1. As can be seen from Table 2, it is difficult for ions to corrode the surface of the substrate. The fact that no inductive arc is generated in the low-frequency stage of the Nyquist diagram confirms this, indicating that no pitting corrosion is induced by the sample. The results of the AC impedance spectrum fitting are consistent with the trend and fitting results of the aforementioned dynamic potential polarization curve.
[0104] Table 2 Electrochemical impedance spectroscopy fitting results of samples
[0105]
[0106] According to the above test results, the results of the potentiodynamic polarization curve of the sample show that no obvious passivation film is formed on the sample under the experimental corrosion conditions, and the electrode activity is only controlled by activation; the electrochemical impedance fitting results show that the sample does not induce pitting corrosion under the experimental corrosion conditions, which is consistent with the results of the potentiodynamic polarization curve. The test results show that the sample has excellent pitting corrosion resistance.
[0107] In summary, the steel plate of the present invention adopts a low-carbon, low-silicon, medium-chromium cheap chemical composition design, and does not contain precious corrosion-resistant metal elements such as Ni, which greatly reduces the material cost; the present invention does not adopt the traditional Al deoxidation technology, but instead uses Si deoxidation, and composite deoxidation supplemented by Ti-RE to form fine, dispersed and uniform composite oxysulfides, which greatly reduces the density of corrosion-active inclusions and significantly improves the crude oil corrosion resistance. This kind of high-strength steel is particularly suitable for use in hydrogen-rich and polychloride ion environments such as crude oil cargo tanks, inferior crude oil refining pipelines, tobacco processing containers and pipelines, hydrogen transportation pipelines and containers, and has excellent resistance to hydrogen embrittlement, acid resistance, and chloride ion resistance.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A medium chromium high strength steel having excellent resistance to oil corrosion and hydrogen induced cracking, characterized in that: Its chemical composition by mass percentage is: 0.011% < C < 0.069%, 0.11% < Si < 0.29%, 0.011% < Mo + Cu < 0.49%, 1.51% < Cr < 1.99%, 0.041% < Ti < 0.059%, 0.005% < RE < 0.019%, S ≤ 0.0010%, and the rest is Fe and inevitable impurities. At the same time, the above chemical composition also satisfies the formula: by mass percentage, Cu / Mo = 1 - 2; The microstructure type of the medium-chromium high-strength steel is a composite microstructure type of acicular ferrite and polygonal grain boundary ferrite, where the area ratio of acicular ferrite is ≥ 85%; The density of corrosion active inclusions in the medium chromium high strength steel is ≤2 pieces / mm 2 ; The saturated current density of the medium-chromium high-strength steel at the static electrode potential E = -300 mV is ≤ 5.0 mA.
2. The medium-chromium high-strength steel with excellent oil corrosion resistance and hydrogen-induced cracking resistance according to claim 1, characterized in that: RE is lanthanum, cerium, or a mixture of lanthanum and cerium.
3. A method for preparing the medium chromium high strength steel having excellent oil corrosion resistance and hydrogen induced cracking resistance according to any one of claims 1 to 2, characterized in that: It includes the following steps: 1) Smelt, refine, and vacuum-treat the molten steel in sequence, and then continuously cast it into a billet; 2) Conduct conventional heating and soaking of the billet; 3) Continuously roll the billet into a product steel plate, and control the finish rolling temperature to be 750 - 850 °C, and water-cool it to 410 - 550 °C after rolling; 4) Naturally cool the steel plate to room temperature to obtain it.
4. The preparation method according to claim 3, characterized in that: The smelting in step 1) specifically includes the following steps: Use a converter or an electric arc furnace to adjust the temperature and composition of the molten steel after smelting the hot metal, scrap steel, or hot metal and scrap steel together. Adjust the tapping temperature to 1585 - 1675 °C, and the free oxygen content in the molten steel is 150 - 390 ppm; After the molten steel enters the ladle, stir it with micro-submerged bubbles for 4 - 8 minutes, and then pre-deoxidize it with Fe-Si alloy or Fe-Si-Mn alloy in the ladle to adjust the free oxygen content in the molten steel to 50 - 90 ppm. After stirring with micro-submerged bubbles for 4 - 6 minutes, use Ti-RE composite alloy for final deoxidation to obtain molten steel that meets the above chemical composition; The Ti-RE composite alloy is added to the molten steel in the form of a massive alloy or a cored wire, and the particle size of the Ti-RE composite alloy is 8 - 16 mm; The addition amount of the Ti-RE composite alloy is 1.2 - 4.8 kg per ton of molten steel.
5. The preparation method according to claim 3 or 4, characterized in that: The refining method is VD refining after LF refining, or the refining method is RH refining after LF refining, and the molten steel after VD refining or RH refining is continuously cast according to the conventional process.
6. Use of the medium chromium high strength steel having excellent oil corrosion resistance and hydrogen induced crack resistance according to any one of claims 1 to 2, characterized in that: As a material for the cargo oil tank of a crude oil tanker, a pipeline material for refining inferior crude oil, a container material for tobacco processing, a pipeline material for tobacco processing, a pipeline material for hydrogen transportation, or a container material for hydrogen transportation.
Citation Information
Patent Citations
High-strength and high-plasticity hot-rolled strip steel with high weather resistance and manufacturing method of high-strength and high-plasticity hot-rolled strip steel
CN115141974A